A proposition of an emerging technologies expectations model: an example of student attitudes towards blockchain - Dymek, Dariusz; Grabowski, Mariusz; Paliwoda-Pękosz, Grażyna (Technological and Economic Development of Economy, 2022)
The paper proposes an Emerging Technologies Expectations Model (ETEM) that aims at explaining the differences in perception of new technologies as well as the expectations towards them. These Expectations, classified into Technology Evolution, Technology Revolution, Social Evolution and Social Revolution are explained by Knowledge and Usage that in turn are shaped by Information Sources. The Information Sources factor, which influences both Expectations and Knowledge, and the Usage factor both play an important role in the model. The application of this model was illustrated using blockchain as an example of an emerging technology, and data from a survey conducted among IT university students in Cracow, Poland. The proposed model contributes to filling the research gap concerning a comprehensive explanation of people’s expectations towards emerging technologies, considering the way people absorb knowledge and undertake the usage of technology based on various information sources. It also provides practical implications, since the knowledge of the factors that can influence people’s expectations towards emerging technologies might be useful in shaping these expectations. First published online 15 November 2021